Isolipoic acid-linked gold nanoparticles bearing the thomsen friedenreich tumor-associated carbohydrate antigen: Stability and in vitro studies - Mondal, Utpal K.; Barchi, Joseph J. (Frontiers in Chemistry, 2022)
We have previously prepared gold nanoparticles (AuNPs ) bearing the Thomsen-Friedenreich antigen disaccharide (TFag), a pan-carcinoma, Tumor-Associated Carbohydrate Antigen (TACA), as tools for various assays and biological applications. Conjugation to AuNPs typically involves the use of thiols due to the affinity of sulfur for the gold surface of the nanoparticle. While a use of a single thiol-containing ligand bound to the gold surface is standard practice, several studies have shown that ligands bearing multiple thiols can enhance the strength of the conjugation in a nearly linear fashion. (R)-(+)-alpha-Lipoic acid (LA), a naturally occurring disulfide-containing organic acid that is used as a cofactor in many enzymatic reactions, has been used as a linker to conjugate various molecules to AuNPs through its branched di-thiol system to enhance nanoparticle stability. We sought to use a similar system to increase nanoparticle stability that was devoid of the chiral center in (R)-(+)-alpha-lipoic acid. Isolipoic acid, an isomer of LA where the exocyclic pentanoic acid chain is shifted by one carbon on the dithiolane ring to produce an achiral acid, was thought to act similarly as LA without the risk of any contaminating (L)-(-) isomer. We synthesized AuNPs with ligands of both serine and threonine glycoamino acids bearing the TFag linked to isolipoic acid and examined their stability under various conditions. In addition, these particles were shown to bind to Galectin-3 and inhibit the interaction of Galectin-3 with a protein displaying copies of the TFag. These agents should prove useful in the design of potential antimetastatic therapeutics that would benefit from achiral linkers that are geometrically linear and achiral.